123 Years of Jamiat Kheir: Service to Education Synergy for Reinvention of Excellence - Hariyadi; Umar Al Haddad; Moh Zamroni (MultiTech Publisher, 2024)
This article explores the 123-year journey of Jamiat Kheir, the oldest Islamic educational institution in Indonesia, in the context of service for education and synergy for reinvention of excellence. Through historical document analysis, in-depth interviews, and participant observation, this study reveals Jamiat Kheir's contribution in shaping the landscape of Islamic education in Indonesia and its strategies for maintaining its relevance in the modern era. The findings show that Jamiat Kheir's success is based on four key strategies: (1) implementing the concept of service in the curriculum, emphasizing the value of service and community service; (2) adapting the curriculum that integrates traditional religious education with modern science; (3) developing innovative programs that respond to contemporary needs; and (4) building synergy with various institutions. This study contributes to the understanding of the evolution and sustainability of Islamic educational institutions in Indonesia, highlighting the importance of reinvention and synergy in facing the challenges of modernization and globalization. The implications of this study can be a model for other Islamic educational institutions in maintaining relevance amidst rapid social and technological changes.